Irony in the emotive vocabulary of the Kabardian-Circassian language - Мadina H. Tokmakova; Boris Ch. Bizhoev (Кавказология, 2024)
This article explores irony in the emotive vocabulary of the Kabardian-Circassian language. The connection between the expression and perception of irony and the cultural prerequisites of society has been noted. The dual function performed by irony in emotive vocabulary is noted. Using examples from Kabardian fiction, the main ways and means of expressing irony (metaphor, hyperbolic comparison, personification, various stylistic figures, graphic symbols), its types (irony, self-irony, author’s irony) are considered. Mention is made of the frequent proximity of irony to lies and their use in manipulation. It is shown how in emotive texts the implementation of dictionary emotive semantics occurs, but most often how vocabulary units not marked with emotivity “acquire” emotive-connotative meanings. The influence of irony on the development of metaphorical meanings of polysemantic words and enantiosemy has been revealed.